2022
DOI: 10.30955/gnj.003929
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of magnesium oxide nanoparticles using leaves of Iresine herbstii for remediation of Reactive Brown 9 dye

Abstract: <p>Nanotechnology is the newest and one of the most promising areas of research in modern medical sciences. Metal nanoparticles possess extraordinary optical, thermal, chemical properties and are being widely used in industrial, electronics, and biomedical fields. It has presented its potential to contribute to solving one of the greatest problems of the worldwide wastewater treatment issue. The approach of green synthesis of metal oxide nanoparticles seems to be a cost-efficient, eco-friendly, and easy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Singh et al [49] reported the removal of numerous harmful metal ions from wastewater using porous ZnO nano-assemblies, including Co2+, Ni2+, Cu2+, Cd2+, Pb2+, Hg2+, and As3+. It has been claimed that Hg2+, Pb2+, and As3+ demonstrate superior removal efficiency (63.5% Hg2+, 100% Pb2+, and 100% As3+) because of their stronger attraction to ZnO nano-assemblies due to their high electronegativity.…”
Section: Zinc Oxide (Zno) Based Nanoparticlesmentioning
confidence: 99%
“…Singh et al [49] reported the removal of numerous harmful metal ions from wastewater using porous ZnO nano-assemblies, including Co2+, Ni2+, Cu2+, Cd2+, Pb2+, Hg2+, and As3+. It has been claimed that Hg2+, Pb2+, and As3+ demonstrate superior removal efficiency (63.5% Hg2+, 100% Pb2+, and 100% As3+) because of their stronger attraction to ZnO nano-assemblies due to their high electronegativity.…”
Section: Zinc Oxide (Zno) Based Nanoparticlesmentioning
confidence: 99%